Effectiveness of non-pharmacological therapies on cognitive function in patients with dementia—A network meta-analysis of randomized controlled trials - Luo, Guangxin; Zhang, Junqiu; Song, Zeyi; Wang, Ying; Wang, Xiaojing; Qu, Haifeng; Wang, Fang; Liu, Chengjiang; Gao, Fujia (Frontiers in Aging Neuroscience, 2023)
Objective Non-pharmacological therapies (NPTs) have received increasing attention from researchers as a category of treatment to improve cognitive impairment in patients with dementia because of their fewer side effects. In this study, photobiomodulation (PBM), enriched environment (EE), exercise therapy (ET), computerized cognitive training (CCT), and cognitive stimulation therapy (CST) were selected to compare the effects of NPTs that improve dementia by quantifying information from randomized controlled trials (RCTs). Methods We did a systematic review and network meta-analysis. We searched PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure Database, Wan Fang Database, Chinese Biomedical Literature Database, Web of Science, and VIP Database from the time of database creation to 1 August 2022. Two investigators independently screened the literature, extracted information, and assessed the RCTs’ quality with the Cochrane Collaboration Network Risk of Bias 2.0. Network meta-analysis was performed using R language (X64 version 4.1.3) and STATA 17.0. Results We identified 1,268 citations and of these included 38 trials comprising 3,412 participants. For improving dementia, the results of the network meta-analysis showed that compared with the control group (CON), PBM (SMD = 0.90, 95% CI: 0.43–1.37), EE (SMD = 0.71, 95% CI: 0.02–1.41), ET (SMD = 0.42, 95% CI: 0.16–0.68), and CST (SMD = 0.36, 95% CI: 0.11–0.62) were significantly different (P < 0.05); There was no significant difference in CCT (SMD = 0.41, 95% CI: −0.07–0.88) (P > 0.05). The ranked results showed that PBM has more potential to be the best intervention (P = 0.90). In addition, there was a significant difference between PBM and CST in improving cognitive function (SMD = 0.54, 95% CI: 0.00; 1.08, P < 0.05). Conclusion In this study, NPTs have excellent potential to improve cognition in people with dementia, and PBM may have more significant benefits in improving cognition than the other four NPTs. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022363746.